Impact of age, tenure and engagement on training transfer and employee performance in South Africa - Harrypurshad, Anil (My University, 2015)
A firm‟s strategy has to keep pace with changes occurring in today‟s rapidly changing business landscape. To achieve success organisations have to leverage all means at their disposal including human resources. Employee development and engagement have long been regarded as major contributors to organisational performance. Employee engagement in particular has received much attention from organisations as a key tool to improve performance. Organisations have spent millions on improving engagement with moderate success in some instances. This report gives a different perspective and also looks at the contribution made by training transfer, thus allowing employers to focus in terms of the antecedents of employee performance towards leveraging the best return. This study was conducted in Gauteng province, South Africa and examines the impacts of employee training transfer and engagement on performance. Employee role behaviours are used as proxies for performance. The impact of age and tenure on these relationships is also examined. The research methodology utilised is quantitative with a positivist approach. Data was collected via an online survey of respondents from various industry segments. Correlation, regression and moderation analysis was utilised to represent, estimate and test the relationships driving employee performance. The moderating effect of age and tenure on these relationships was also examined. Key findings within the research indicate that a link exists between training transfer, engagement and performance which may deserve employers‟ attention. The findings are consistent with existing literature. Employee behaviour was used as a proxy for performance and shows the extent to which training transfer and employee engagement influences it. We found that training transfer and generalisation is closely associated with positive workplace behaviours such as organisation citizenship behaviour and in-role behaviours and negatively related to counterproductive work behaviours. The moderating effect on the transfer – performance and engagement –performance relationships by age and tenure was confirmed. Older employees were found to iii have a greater degree of training transfer and performance while younger employees were more engaged. The key finding being that the transfer of learnt skills may have a greater influence on performance than employee engagement. Thus, in conclusion, this study may positively influence the way organisations focus their employee performance improvement efforts. This may allow for a greater investment return and maximise performance improvement opportunities. Employers‟ obsession with engagement as the most effective tool to improve performance has been questioned in the results of the study. It may allow employers to include training transfer evaluation as part of performance improvement initiatives. The reluctance of employers to employ older workers is also brought into question with these results. The benefit of the study, to business, is that it allows organisations to re-evaluate where they spend available funds to maximise performance i.e. engagement or training transfer and generalisation to obtain greatest impact. The influences of organisational climate and practices also play a key role. It also allows organisations to revisit their recruitment practices, given some of the findings. However it must be noted that there are limitations to these findings and key decisions must be evaluated using organisational data before implementation but the study does provide some questions regarding conventional human resource thinking around the benefits of employee engagement initiatives as opposed to training transfer initiatives.
Keywords: Employees -- Training of -- South Africa. Employee motivation -- South Africa. Organizational effectiveness -- South Africa.